The Role of Vocational Education in NEP 2020: Pathways to Skill Development and Employment - Kadam, Sangeeta Rajaram (AG Volumes, 2025)
By emphasising skill-based learning to bridge the gap between knowledge and practical application, the National Education Policy (NEP) 2020 transforms India's education system. Recognising these issues, the strategy attempts to provide students with vital skills to improve employability and help them choose careers. NEP 2020 wants to turn India's young into global resources via innovation, curiosity, and hands-on learning. By integrating vocational education at all levels, the approach ensures that every student graduates with a skill. Skill development is anticipated to eliminate unemployment and advance the country. Additionally, NEP 2020 prioritizes teacher training programs to enhance the quality of vocational education and align curricula with national skill standards. The adoption of Open and Distance Learning (ODL) through the National Institute of Open Schooling (NIOS) further extends vocational education opportunities to marginalized communities, school dropouts, and rural populations. By offering skill-based courses in fields such as agriculture, IT, healthcare, and manufacturing, ODL provides flexible and inclusive learning pathways beyond traditional classroom settings.